Optimasi Kandungan Gizi Susu Kambing Peranakan Etawa Menggunakan Extreme Learning Machine Dan Improved-Particle Swarm Optimization - Bayu Andika Paripih; Imam Cholissodin; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Milk is source of protein which is contain all of easy digested and required nutrition. Milk production by dairy cows are low so Indonesian need of milk can't be fulfilled. PE goat can produce qualify milk cow and it also suitable to be cultivated at Indonesia so they can be alternative of milk source. Produced milk quality is affected by given feed. This research uses Extreme Learning Machine and Improved-Particle Swarm Optimization to search best feed composition so the goat can produce good milk. Parameter calibration for building model are hidden node = 9, population size 70, maximum iteration 40 with fitness value 0.973892. Parameter calibration for searching feed composition are population size = 90 and maximum iteration 20 with fitness value 38,51344218.